2013
DOI: 10.1186/2192-5372-2-5
|View full text |Cite
|
Sign up to set email alerts
|

Young women in science and technology: the importance of choice

Abstract: Despite significant improvements in the last couple of years, women are still under-represented in science and technology, both in the academic and private sector. This is due to a variety of reasons, mostly related to the role allocated to women in modern society as well as pre-existing prejudices that form glass ceilings while encouraging male presence in the workplace. It is also however, a result of information or lack of, which places young women in difficult position of making a career choice, with littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 10 publications
3
13
1
4
Order By: Relevance
“…Boys, it appears, look towards parents and guardians for insight and guidance towards their future career path. These results differ from Dimitriadi (2013) who suggested that cultural influences are strong especially when related to parental roles.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…Boys, it appears, look towards parents and guardians for insight and guidance towards their future career path. These results differ from Dimitriadi (2013) who suggested that cultural influences are strong especially when related to parental roles.…”
Section: Discussioncontrasting
confidence: 94%
“…Role models contribute to Year 11 girls' decisions about their future career; however, when the ICT industry is lacking in high profile younger role models, it is not surprising that fewer girls want to pursue ICT as a career. This supports findings by Dimitriadi (2013) related to culture, especially for nonwesternised cultures and looking up to family members as role models; however, Perciva (2014) found girls have turned off STEM subjects when pretty young females were roles model. This could indicate a difference in western culture compared to other cultures.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations